Cardiovascular imaging of women and men visiting the outpatient clinic with chest pain or discomfort: design and rationale of the ARGUS Study. Issue 12 (15th December 2020) - Groepenhoff, Floor; Eikendal, Anouk L M; Bots, Sophie Heleen; van Ommen, Anne-Mar; Overmars, L M; Kapteijn, Daniek; Pasterkamp, Gerard; Reiber, Johan H C; Hautemann, David; Menken, Roxana; Wittekoek, Marianne E; Hofstra, Leonard; et al.
Abstract : Introduction: Chest pain or discomfort affects 20%–40% of the general population over the course of their life and may be a symptom of myocardial ischaemia. For the diagnosis of obstructive macrovascular coronary artery disease (CAD), algorithms have been developed; however, these do not exclude microvascular angina. This may lead to false reassurance of symptomatic patients, mainly women, with functionally significant, yet non-obstructive coronary vascular disease. Therefore, this study aims to estimate the prevalence of both macrovascular and microvascular coronary vascular disease in women and men presenting with chest pain or discomfort, and to subsequently develop a decision-support tool to aid cardiologists in referral to cardiovascular imaging for both macrovascular and microvascular CAD evaluation. Methods and analysis: Women and men with chest pain or discomfort, aged 45 years and older, without a history of cardiovascular disease, who are referred to an outpatient cardiology clinic by their general practitioner are eligible for inclusion. Coronary CT angiography is used for anatomical imaging. Additionally, myocardial perfusion imaging by adenosine stress cardiac MRI is performed to detect functionally significant coronary vascular disease. Electronic health record data, collected during regular cardiac work-up, including medical history, cardiovascular risk factors, physical examination, echocardiography, (exercise) ECG and blood samples for standard cardiovascular biomarkers and research purposes, are obtained. Participants will be classified as positive or negative for coronary vascular disease based on all available data by expert panel consensus (a cardiovascular radiologist and two cardiologists). After completion of the clinical study, all collected data will be used to develop a decision support tool using predictive modelling and machine-learning techniques. Ethics and dissemination: The study protocol was approved by the Institutional Review Board of the University Medical Center Utrecht. Results will be disseminated through national and international conferences and in peer-reviewed journals in cardiovascular disease. Trial registration number: Trialregister.nl Registry NL8702.